Rock Formation Acid Mine Drainage in Epithermal Gold Mineralization, Pandeglang, Banten Province - Dudi Nasrudin Usman; Sri Widayati; Sriyanti Sriyanti; Era Setiawan (UIR PRESS, 2019)
Mine acid water is acidic water and contains iron and sulfate, which is formed under natural conditions when geological strata containing pyrites are exposed to an oxidizing atmosphere or environment. One of the impacts of the mineralization zone where there is a mining process is the potential for the formation of acid mine drainage, especially in the Cibaliung gold mineralization area and its surroundings, Pandeglang Regency, Banten Province. Acid-forming sulfide minerals include pyrite (FeS2), headquarters (FeS2), picoliters (FexSx), calcocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), chalocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), chalocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), galena (PbS) ) and sphalerite (ZnS). Of all these minerals, pyrite is the most dominant sulfide in acid formation. Alkaline mine water (alkaline mine drainage) is mine water that has an acidity level (pH) of 6 or more, containing alkalinity but still containing dissolved metals that can produce acids. The quality of mine water, acid or alkali, depends on the presence or absence of acid mineral content (sulfides) and alkaline materials in the geological strata. Acid water formation tends to be more intensive in mining areas. This can be prevented by avoiding exposure to sulfide-containing materials in the free air. Acid-forming sulfide minerals include pyrite (FeS2), headquarters (FeS2), picoliters (FexSx), calcocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), chalocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), chalocytes (CuS), covellite (CuS), chalcopyrite (CuFeS2), molybdenite (MoS), mulenite (NiS), galena (PbS) ) and sphalerite (ZnS). Of all these minerals, pyrite is the most dominant sulfide in acid formation. Formation of potential acidic water also occurs in tailings which are residues/processing residues containing sulfide minerals. The formation of acid mine drainage does not always develop in every sulfide-ore mining. In certain types of ore deposits, there are neutralizing agents which prevent the formation of acid mine drainage.